PERAN ORANG TUA DALAM MENDORONG MOTIVASI BELAJAR SISWA SD - Siti Qomariyah; Deni Adi Putra; Fajar Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study was conducted as a literature analysis aimed at elu-cidating the role of parents in fostering students' learning moti-vation at the elementary school level based on findings from various articles. To achieve this objective, the study adopts a qualitative approach, focusing on the detailed description, iden-tification, and in-depth exploration of findings from previous studies. The sources used in this research include journals and articles. The data analysis process in this literature review in-volves several stages, such as source identification, literature selection, synopsis creation, theme synthesis, comparative analysis, conclusion formulation, and evaluation of the source's credibility. The study reveals that parental involvement directly contributes to students' learning motivation, analyzed using quantitative and qualitative methods. The importance of paren-tal support in the educational process is crucial; however, it of-ten faces obstacles such as parents' busy schedules and a need for more awareness regarding the importance of educa-tion.